ANALISIS STRATEGI MARKETING MEDIA SOSIAL TERHADAP MINUMAN KESAYANGAN CABANG LAU DENDANG KEC PERCUT SEI TUAN SUMATERA UTARA - Padila Putri; Siska Aliya Damayanti; Yogi Agung Pradana; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Marketing via social media is a form of digital marketing strategy where business people use social media and websites to promote their business, products or services. This research aims to find out whether the beloved beverage business uses social media marketing strategies in carrying out promotions. The method used in this research is qualitative with an interview method, namely a direct interview technique with a respondent using several questions. The results of this research show that the Lau Dendang Branch of Favorite Drinks uses social media marketing strategy techniques to attract customers by sharing promotions via their social media. This shows that promotion through social media is very effective.